Exploring assessment for learning in one higher education classroom - Koen, Magaretha Paulina (Stellenbosch : University of Stellenbosch, 2011)
ENGLISH ABSTRACT: Assessment, teaching and learning are key elements in lecturers' pursuit of quality in education. In fact, Black and Wiliam (1998) argue that assessment, a vital part of this reciprocal relationship should contribute to classroom learning rather than concentrate on restricted forms of tests that are not always linked to a student's learning experience. It is therefore open to debate whether a handwritten, one-hour examination does indeed stimulate students to learn and develop the knowledge, the understanding, the attitudes and the skills they need to develop. This statement mirrors the hotly debated and contradictory role of the lecturer of simultaneously having to both judge and support students' learning. In addition, widespread social and political turbulence and changes have played a role in the reform of assessment in South Africa during the past 20 years. It seems as if lecturers are caught in the middle of this conflicting role where they are expected to navigate themselves and their students through the uncertainty about how assessment should be organised, while at the same time being accountable to the students, parents, and the institution. Given the above background, the following question arises: "How can assessment enhance learning in one higher education classroom?" In answering this question, a basic interpretative qualitative approach employing focus groups and semi-structured interviews, was used in order to explore - through a variety of lenses - how final-year students in one higher education classroom dealt with assessment issues. This study aimed at using appropriate measures to conduct research to establish a chain of evidence (forward and backward) by implementing Lincoln and Guba's model for trustworthiness (1985). The conceptual framework for this study was mainly drawn from Race.s spreading ripples model of learning. The underlying premise of Race's theory is based on the idea that effective learning demands the dynamic interaction of four elements like the ripples on a pond, namely wanting/ needing, doing, feedback and digesting. The findings of the study suggested that assessment of a Life Skills Module should provide students with a variety of opportunities to demonstrate their learning in order to develop a well-rounded set of abilities when they enter the workplace. This idea signaled the importance of bearing in mind the first and foremost purpose of assessment, namely that assessment should serve student learning.